Effect of salt content on gelation of normal and wooden breast myopathy chicken pectoralis major meat batters. (18th June 2017) - Xing, Tong; Zhao, Xue; Cai, Linlin; Guanghong, Zhou; Xu, Xinglian
Summary: This study investigated the effects of salt content (0–4%) on water holding capacity (WHC), textural characteristics, rheological properties, and microstructure of cooked normal (NOR) and wooden breast (WB) chicken meat batters. Results indicated with 0–2% salt addition, the WB batters had significantly lower WHC and storage modulus (G') compared with the NORs ( P < 0.05). However, these differences were eliminated when salt contents were increased to 3% or 4%. In addition, the NORs formed more regular and pored networks than the WBs (0–2%). Salt level significantly affected the textural properties of both batter types ( P < 0.05). The hardness of the WB batters was lower than NORs at all NaCl levels ( P < 0.05). Overall, compared with NORs, the WB batters showed inferior gelation properties at salt contents of 0–2%, while increasing salt content to 3–4% can improve the WHC and microstructure of gels. Abstract : The figure indicates the effects of salt content (0‐4%) on water holding capacity, textural characteristics, rheological properties, and microstructure of cooked normal and wooden breast chicken meat batters.